Effect On Young Children's Creativity Through Computer-Rich Learning Environment: A Malaysian Pre-School Perspective - Song, Helena Sook Yee (2005)
The purpose of this research study is to shed some light on how we utilize computers appropriately to enhance young children's learning and development, especially on the development of creativity. This study examines the effect of using developmentally appropriate software on young children's creativity.